The Shoes in Sikh Way : the Philosophy from Punjab to Chao Praya - คําวัง อภิรัฐ (Journal of the Faculty of Arts, Silpakorn University, 2020)
Some of the philosophy and Guru’s teachings in Sikhism emphasize the socialization process and self control in which the five cardinal vices must be destroyed, especially the ego’s Ahankar (pride). Ahankar destruction could be done in various ways. One of them is by voluntarily and heartily serving the society. The article is concerned with the collection of shoes from the visitors at the Gurudwara in Bangkok where all walks of life participate in the shoe room eagerly and voluntarily. Touching and cleaning shoes offers an opportunity for the Ahankar destruction, and will eventually lead the way to the practice of the Guru’s teachings of humbleness.